Associations Between Thyroid Volume and Physical Growth in Pubertal Girls: Thyroid Volume Indexes Need to Be Applied to Thyroid Volume Assessments - Wang, Yingying; Dong, Xiaolian; Fu, Chaowei; Su, Meifang; Jiang, Feng; Xu, Dongli; Li, Rui; Huang, Peixin; Wang, Na; Chen, Yue; Jiang, Qingwu (Frontiers in Endocrinology, 2021)
Background: Thyroid volume (Tvol) is associated with many factors, but the current reference values for Tvol in children with sufficient iodine intake are inappropriate and need to be updated. Moderate changes in thyroid morphology and accentuated increases in body fat percentage occur during puberty as an adaption to body and sexual development. The study aimed to evaluate the influences of physical growth on Tvol and propose a well-applicable method for Tvol assessments in pubertal girls with sufficient iodine intake. Methods: A cohort study was conducted in 481 pubertal girls in East China from 2017 to 2019. B-ultrasound was used to assess Tvol. Multiple linear regression models were used to estimate the associations of Tvol enlargement (dTvol) with changes in height (dH), weight (dW), waist circumference (dW), body mass index (dBMI) and body surface area (dBSA). Thyroid volume indexes (TVIs), including height thyroid volume index (HVI), weight and height thyroid volume index (WHVI), body mass index thyroid index (BMIV) and body surface area thyroid index (BSAV), were calculated to explore an appropriate method for Tvol assessments by Spearman correlation analyses. Results: Tvol, height, weight, BMI and BSA increased significantly from baseline to follow-up (P<0.001). The associations between dTvol and physical growth were only observed in the 13 to 14-year-old group. dH, dW,dBMI and dBSA were positively related to dTvol, with the maximum β of 5.74 (95%CI: 2.54 to 8.94) on dBSA, while dWC was negatively related to dTvol (β= -0.05, 95%CI: -0.08 to -0.03). Both dHVI and dBSAV were not associated with dH, dW, dBMI or dBSA in both age group (P>0.05). Conclusions: Thyroid volume was associated with physical growth in pubertal girls in East China, both age and anthropometric measurements must be comprehensively considered to establish the reference values for Tvol. HVI and BSAV may be the better indicators for Tvol assessments in pubertal girls.